Fish intestine miRNome: disentangling the microRNAS role between host and microbiota interplaying in Atlantic salmon fed with functional diets - Gonçalves - Fachadas Gato, Ana Coelho (2021)
FONDECYT de Iniciación 2016 Proyectos de Investigación Functional diets mirna host-microbiota interactions Fish Nutrition & Health Nutrigenomics Microbiology Proyectos de Investigación Finalizado